2013
DOI: 10.1007/s00401-013-1228-0
|View full text |Cite
|
Sign up to set email alerts
|

Embryonal tumor with abundant neuropil and true rosettes (ETANTR), ependymoblastoma, and medulloepithelioma share molecular similarity and comprise a single clinicopathological entity

Abstract: Three histological variants are known within the family of embryonal rosette-forming neuroepithelial brain tumors. These include embryonal tumor with abundant neuropil and true rosettes (ETANTR), ependymoblastoma (EBL), and medulloepithelioma (MEPL). In this study, we performed a comprehensive clinical, pathological, and molecular analysis of 97 cases of these rare brain neoplasms, including genome-wide DNA methylation and copy number profiling of 41 tumors. We identified uniform molecular signatures in all tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
188
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 191 publications
(196 citation statements)
references
References 29 publications
6
188
1
1
Order By: Relevance
“…Notably, we and others have identified a subtype of CNS-PNETs (which we call Group 1 CNS-PNETs) distinguished by hallmark genomic amplification of the embryonic stem cell (ES)-enriched C19MC oncogenic miRNA cluster and histological features reminiscent of very early neural differentiation [3,4]. Significantly in recent studies, we observed C19MC amplification in CNS-PNETs with different histologic diagnostic labels, including ETANTRs, ependymoblastoma and medulloepithelioma, originating in various CNS locations [5,6]. These Group 1 tumors collectively comprise~25% of all CNS-PNETs arising in very young children (> 80% are < 4 years old), and are distinctly lethal tumors with characteristic rapid disease tempo.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Notably, we and others have identified a subtype of CNS-PNETs (which we call Group 1 CNS-PNETs) distinguished by hallmark genomic amplification of the embryonic stem cell (ES)-enriched C19MC oncogenic miRNA cluster and histological features reminiscent of very early neural differentiation [3,4]. Significantly in recent studies, we observed C19MC amplification in CNS-PNETs with different histologic diagnostic labels, including ETANTRs, ependymoblastoma and medulloepithelioma, originating in various CNS locations [5,6]. These Group 1 tumors collectively comprise~25% of all CNS-PNETs arising in very young children (> 80% are < 4 years old), and are distinctly lethal tumors with characteristic rapid disease tempo.…”
mentioning
confidence: 70%
“…Notably, recent studies demonstrate C19MC-associated Group 1 tumors with various histologic labels and anatomic location exhibit a common transcriptional and epigenomic signature, distinct from that of other CNS-PNETs, thus indicating these tumors comprise a common molecular disease [5,6]. Consistent with their distinctly primitive histology, transcriptional signatures of C19MC-associated tumors show most remarkable enrichment of pluripotency and early neural differentiation genes.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…3 ETANTR is an aggressive variant of CNS-PNET characterized by the presence of primitive tumor cells with a small-cell phenotype, abundant neuropil, and ependymoblastic rosettes. 26 The tumor is characterized by a specific amplicon of a microRNA locus on chromosome 19 (C19MC). 26 Interestingly, we also identified a patient with a Wnt-medulloblastoma in the brainstem, which is distinct from fourth ventricular medulloblastomas with brainstem invasion (Fig.…”
mentioning
confidence: 99%
“…26 The tumor is characterized by a specific amplicon of a microRNA locus on chromosome 19 (C19MC). 26 Interestingly, we also identified a patient with a Wnt-medulloblastoma in the brainstem, which is distinct from fourth ventricular medulloblastomas with brainstem invasion (Fig. 5).…”
mentioning
confidence: 99%